The Types of Figurative Language with References to Six The Weeknd Songs - Siut, Afrilasiana; I Gusti Ayu Vina Widiadnya Putri; I G B Wahyu Nugraha Putra (Institut Pariwisata dan Bisnis Internasional, 2025)
The purpose of this study is to identify the types and analyze the meaning of figurative language that appeared in six songs by The Weeknd. This study used a qualitative method by using two theories. The first theory is about the theory of figurative language by X. J. Kennedy (1979), which is used to identify the types of figurative language in four songs by The Weeknd. Meanwhile, another theory is the theory of meaning by Leech (1981), which is used to analyze the meaning of figurative language in four songs by The Weeknd. The data used in this study was taken from four songs by The Weeknd. In collecting the data, documentation techniques were used in this study. The study's findings indicate that The Weeknd uses four different types of figurative language in four of his songs: simile, personification, hyperbole, and metaphor.There are 8 figurative languages appeared in the song lyrics. one (1) lyric is identified as simile, one lyric (1) is identified as personification, and five (5) lyrics are identified as as hyperbole, and one (1) lyric is identified as metaphor. Hyperbole is the highest dominant type and appears in four of The Weeknd's songs.